Risk, Trust, and Consumer Online Purchasing Behaviour of Consumers in Indonesia - , STEFANI PASKALIA WIDIYANI, Dr. Sahid Susilo Nugroho, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Shopping online has been seen as the new way of shopping alongside with the development of the internet. Some people may see online shopping as cheaper and beneficial as customers are given the opportunity to price-match across the web, keep track of their order more conveniently through credit card purchase records, be allowed to see whether the goods they want are available before making any purchases. Shopping online has also affected the behaviour of consumers. The objective of this research is to evaluate consumersâ online purchasing behaviour. This is done through analyses of perceived risk and trust and its relation with the repetition of purchasing online, among consumers in Indonesia. In addition, this research also addresses demands to investigate consumersâ post adoption acceptance of a technology in order to understand which factors in perceived risk and trust are most significant in explaining the longevity of online purchases of consumers. The study took the data from 240 respondents across places in Indonesia. Using Structural Equation Modelling, the model examines the effect of attitude, influenced by perceived risk and trust, on consumers purchasing intentions. The results of this study show that in general, perceived risk and trust have significant influence on consumer intention to continue to use the online shopping facility.